The Effective Theological Proposition in Ijtihad (Comprehensiveness of Religion) - Dr. Ali Reza Saberyan (آموزه‌‌های فقه مدني)
Some of theological propositions directly influence on legal inference. Comprehensiveness and perfection of the religion is one of the theological propositions that have much effect in interpretation of the religious texts. In our idea, religion is for the happiness in this world and Hereafter. In accordance with the comprehensiveness of the religion and this idea, religious texts can be interpreted in this context. Islamic religion has decreed the general and particular orders, but this way of enactment dose not mean that it is enough for all aspects of human life rather it is necessary to be enacted in the framework of religious law. One the important result of the comprehensiveness and perfection of the religion is its containing of the government and executive agency. Accepting of this idea is not meant the establishment of the reasonable rules and principles of the governing, but rather religion can confirm some of the reasonable rules and principles and reject some of them and declare its idea.